'Just an extra pair of hands'? A qualitative study of obstetric service users' and professionals' views towards 24/7 consultant presence on a single UK tertiary maternity unit. Issue 3 (6th March 2018) - Reid, Holly E; Wittkowski, Anja; Vause, Sarah; Heazell, Alexander E P
Abstract : Objectives: To explore the views of maternity service users and professionals towards obstetric consultant presence 24 hours a day, 7 days a week. Design: Semistructured interviews conducted face to face with maternity service users and professionals in March and April 2016. All responses were analysed together (ie, both service users' and professionals' responses) using an inductive thematic analysis. Setting: A large tertiary maternity unit in the North West of England that has implemented 24/7 obstetric consultant presence. Participants: Antenatal and postnatal inpatient service users (n=10), midwives, obstetrics and gynaecology specialty trainees and consultant obstetricians (n=10). Results: Five themes were developed: (1) ' Just an extra pair of hands? ' (the consultant's role), (2) the context, (3) the team, (4) training a nd (5) change for the consultant . Respondents acknowledged that obstetrics is an acute specialty, and consultants resolve intrapartum complications. However, variability in consultant experience and behaviour altered perception of its impact. Service users were generally positive towards 24/7 consultant presence but were not aware that it was not standard practice across the UK. Professionals were more pragmatic and discussed how the implementation of 24/7 working had affected their work, development of trainees and potential impacts on future consultants. Conclusions: The findings raised several issues that should be considered by practitioners and policymakers when making decisions about the implementation of 24/7 consultant presence in other maternity units, including attributes of the consultants, the needs of maternity units, the team hierarchy, trainee development, consultants' other duties and consultant absences.